The Comparison of Financing and System Work Duration Modular Construction With Conventional Construction Systems : (Case Study: Rspp Extension Modular Simprug) - Hijjral Hamdani (Jurnal Mahasiswa Jurusan Arsitektur, 2022)
RSPP Extension Modular Simprug is one of the Covid-19 emergency health infrastructure in Indonesia which was built with a volumetric type modular construction system produced by PT. Wika Building. This modular construction system has various advantages, for example, shorter work duration, relatively cheaper costs compared to conventional construction with savings of up to 40%. Therefore, the purpose of this study is to understand in detail about the volumetric modular used so that a comparison can be made between these two construction systems in terms of the duration of work and the financing required between modular construction and conventional construction. This study uses a descriptive method to explain the modular construction of the study object and a comparative method to compare the two construction systems. From the results of the analysis, it was found that modular construction is indeed faster in duration of work than conventional and also cheaper in terms of cost, although it has not yet reached 40% in terms of cost savings.